2004
DOI: 10.1111/j.0143-2885.2004.00785.x
|View full text |Cite
|
Sign up to set email alerts
|

Survival ofEnterococcus faecalisin infected dentinal tubules after root canal filling with different root canal sealersin vitro

Abstract: Root fillings in vitro with gutta-percha and AH or GS were effective in killing E. faecalis in dentinal tubules. Other endodontic sealers, as well as CH, were less effective.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
119
1
11

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 145 publications
(139 citation statements)
references
References 33 publications
8
119
1
11
Order By: Relevance
“…According to Pizzo et al, (13), AH Plus sealer, used in this study, presents bacterial inhibition within the first 24 hours, which may have delayed bacterial penetration but was not able to completely prevent coronal leakage of E. faecalis. Therefore, an important role of the endodontic obturation is the formation of a physical barrier to prevent bacteria from reaching the apical region and periapical tissues (16). In Group 1 (root filling remnant of 6 mm), this physical barrier was 3 times larger than that in Group 3 (root filling remnant of 2 mm), which may possibility explain the difference observed between these groups at 20 days concerning the number of specimens with bacterial leakage.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…According to Pizzo et al, (13), AH Plus sealer, used in this study, presents bacterial inhibition within the first 24 hours, which may have delayed bacterial penetration but was not able to completely prevent coronal leakage of E. faecalis. Therefore, an important role of the endodontic obturation is the formation of a physical barrier to prevent bacteria from reaching the apical region and periapical tissues (16). In Group 1 (root filling remnant of 6 mm), this physical barrier was 3 times larger than that in Group 3 (root filling remnant of 2 mm), which may possibility explain the difference observed between these groups at 20 days concerning the number of specimens with bacterial leakage.…”
Section: Discussionmentioning
confidence: 96%
“…E. faecalis is the most often retrieved pathogen in asymptomatic endodontic infections because of its capacity to invade dentinal tubules, compete with other microorganisms and resist nutritional privation. It is a facultative anaerobic Gram-positive coccus that may present either isolated, in pairs or in chains (4,16,17,20).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Stevens et al, found that a final rinse with 95% ethanol increased the depth of penetration of a ZnOE based sealers and significantly reduced micro leakage [27]. Tests on dentinal tubule penetration have shown calcium hydroxide based sealers to be less effective in killing bacteria when compared to resin and eugenol based sealers [28,29]. Direct contact tests of sealers and microorganisms concluded calcium hydroxide sealers to be having mild anti-microbial effect over a short duration [30,31].…”
Section: Methodsmentioning
confidence: 99%